Where did it go wrong? Marriage and divorce in Malawi - Laurens Cherchye; Bram de Rock; Frederic Vermeulen; Selma Walther (Quantitative Economics, 2021)
Do individuals marry and divorce for economic reasons? Can we measure the economic attractiveness of a person's marriage market? We answer these questions using a structural model of consumer-producer households that is applied to rich data from Malawi. Using revealed preference conditions for a stable marriage market, we define the economic attractiveness of a potential match as the difference between the potential value of consumption and leisure with the new partner and the value of consumption and leisure in the current marriage. We estimate this marital instability measure for every possible pair in geographically defined marriage markets in 2010. We find that the marital instability measure is predictive of future divorces, particularly for women. We further show that this estimated effect on divorce is mitigated by the woman's age, and by a lack of men, relative to women, in the marriage market, showing that these factors interact with the economic attractiveness of the remarriage market. These findings provide out-of-sample validation of our model and evidence that the economic value of the marriage market matters for divorce decisions.
Keywords: D11; D12; D13; J12; 330; agricultural production; divorce; Malawi; Marriage market; revealed preference